2007
DOI: 10.1111/j.1751-1097.2007.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Protoporphyrin IX (PpIX) Pharmacokinetics After Topical Application of 5‐Aminolevulinic Acid in Urethral Condylomata Acuminata

Abstract: The pharmacokinetics of 5-aminolevulinic acid (ALA)-induced protoporphyrin IX (PpIX) in lesions of urethral condylomata acuminata were investigated. Sixty patients (20 to 60 years old, 48 male and 12 female) were divided randomly into five groups and received topic application of different concentrations of ALA solution (0.5%, 1%, 3%, 5% or 10%). Biopsy was performed between 1 and 7 h and specimens were subjected to histological, PpIX fluorescence and human papillomavirus (HPV) DNA typing analyses. Fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…It has previously been proposed that light activation of the elevated levels of PPIX found in HPV acanthomas can lead to viral inactivation via cellular necrosis and the induction of an immune response in infected keratinocytes, which are the primary epidermal skin cells . Recent studies on urethral condylomata acuminata have shown that PPIX is predominantly located in the epidermis and accumulates in the rete Malpighii, which is the innermost layer of the epidermis, and koilocytes, which are dysplastic squamous cell found in potentially precancerous cervical lesions . The rete Malpighii are the initial infection and replication site of the virus while the koilocytes are involved in virus particle assembly .…”
Section: The Inactivation Of Viruses By Ala‐based Pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been proposed that light activation of the elevated levels of PPIX found in HPV acanthomas can lead to viral inactivation via cellular necrosis and the induction of an immune response in infected keratinocytes, which are the primary epidermal skin cells . Recent studies on urethral condylomata acuminata have shown that PPIX is predominantly located in the epidermis and accumulates in the rete Malpighii, which is the innermost layer of the epidermis, and koilocytes, which are dysplastic squamous cell found in potentially precancerous cervical lesions . The rete Malpighii are the initial infection and replication site of the virus while the koilocytes are involved in virus particle assembly .…”
Section: The Inactivation Of Viruses By Ala‐based Pdtmentioning
confidence: 99%
“…Acne vulgaris associated with P. acnes 96,99,150,[152][153][154]161,165 Chronic folliculitis associated with P. acnes, S. aureus, and some Gram-negative bacteria 147 Gastritis and gastroduodenal ulceration associated with H. pylori infection 170 Lichen sclerosis associated with Borrelia burgdorferi [143][144][145] Skin lesions associated with M. marinum 176,177 MDR, multiple drug resistance; ALA, 5-aminolevulinic acid; MRSA, methicillin-resistant Staphylococcus aureus. 204 Herpes simplex virus and associated infections 81,[204][205][206] , including lip lesions 208 Human papillomavirus (HPV) and associated common warts or verruca vulgaris 53,91,92 HPV and associated anogenital warts or condylomata acuminate 234,323 HPV and associated periungual warts 212 HPV associated cervial and vulval lesions [217][218][219][220] HPV and associated epidermodysplasia verruciformis 224,225 Molluscum contagiosum virus and associated molluscum contagiosum 229…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…The normal tissue and nonin°ammatory cells uptake little to no ALA and show weak or no red°uor-escence. 23,24 This study demonstrated that LP lesions could generate strong PpIX signals (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…This process is very selective and results in minimal damage to surrounding healthy tissues. Also, the recurrence rate is low with this approach, compared to others [12] and can be applied for the treatment of subclinical skin infections. However, ALA-PDT has a major limitation in that it is not optimal for large warts due to its limited depth of penetration into tissue [13,14].…”
Section: Introductionmentioning
confidence: 93%